Proteomic Analysis Reveals That Placenta-Specific Protein 9 Inhibits Proliferation and Stimulates Motility of Human Bronchial Epithelial Cells - Wang, Hai-Xia; Qin, Xu-Hui; Shen, Jinhua; Liu, Qing-Hua; Shi, Yun-Bo; Xue, Lu (Frontiers in Oncology, 2021)
Placenta-specific protein 9 (PLAC9) is a putative secretory protein that was initially identified in the placenta, and is involved in cell proliferation and motility. Bioinformatics analyses revealed that PLAC9 is repressed in lung cancers (LCs), especially lung adenocarcinomas, compared to that in the paired adjacent normal tissues, indicating that PLAC9 might be involved in the pathogenesis of pulmonary diseases. To investigate the potential role of PLAC9 in the abnormal reprogramming of airway epithelial cells (AECs), a key cause of pulmonary diseases, we constructed a stable PLAC9-overexpressing human bronchial epithelial cell line (16HBE-GFP-Plac9). We utilized the proteomic approach isobaric tag for relative and absolute quantification (iTRAQ) to analyze the effect of PLAC9 on cellular protein composition. Gene ontology (GO) and pathway analyses revealed that GO terms and pathways associated with cell proliferation, cell cycle progression, and cell motility and migration were significantly enriched among the proteins regulated by PLAC9. Our in vitro results showed that PLAC9 overexpression reduced cell proliferation, altered cell cycle progression, and increased cell motility, including migration and invasion. Our findings suggest that PLAC9 inhibits cell proliferation through S phase arrest by altering the expression levels of cyclin/cyclin-dependent kinases (CDKs) and promotes cell motility, likely via the concerted actions of cyclins, E-cadherin, and vimentin. Since these mechanisms may underlie PLAC9-mediated abnormal human bronchial pathogenesis, our study provides a basis for the development of molecular targeted treatments for LCs.